Historical development of the usability of audiovisual resources (Digital Networks), as a study and learning technique, by engineering students at colombian universities (2024)
The teaching-learning process has been permeated by technological expressions that allow revealing trends in the forms of relationship between teachers and students; through the use of audiovisual resources inside and outside the classroom. In this sense, based on a quantitative approach methodology, a group of university students from the Faculty of Engineering of the Universidad Cooperativa de Colombia, Bogotá campus, were surveyed to find out their perceptions about the use of audiovisual formats (videos, tutorials, cinema forums), as guided and autonomous study tools to strengthen their professional training process. At the same time, a literary review of an academic type was carried out, around three categories of analysis that were configured in a log of findings; to reference theoretical and scientific postulates around concepts linked to educational innovation, for teaching-learning in university contexts. In general, the research results allowed us to identify not only the preferences of university students, in their moments of learning; but investigative inputs for the development of strategies that can guarantee better teaching processes, for the young people of the current information and knowledge society.